2008
DOI: 10.2337/dc07-1971
|View full text |Cite
|
Sign up to set email alerts
|

HLA Class II Alleles Specify Phenotypes of Ketosis-Prone Diabetes

Abstract: OBJECTIVE -Ketosis-prone diabetes (KPD) comprises four subgroups based on the presence or absence of ␤-cell autoantibodies (Aϩ or AϪ) and ␤-cell functional reserve (␤ϩ or ␤Ϫ). Genetic factors could contribute to their distinctive phenotypes. Our aim was to specify the role of HLA class II alleles associated with susceptibility or resistance to autoimmune type 1 diabetes in determining KPD phenotypes.RESEARCH DESIGN AND METHODS -A total of 185 adults presenting with diabetic ketoacidosis were followed longitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…Hence, absence of GAD65 or IA-2 Abs, even in patients with long-standing diabetes, is probably quite reliable in classifying them as AϪ. To limit further the possibility of misclassifying Aϩ␤Ϫ KPD patients as AϪ␤Ϫ, we have performed extensive HLA typing (1,27) and have found that the frequencies of major class II alleles associated with susceptibility to autoimmune type 1 diabetes are not significantly higher in AϪ␤Ϫ KPD patients than in ethnicmatched population controls, whereas they are significantly higher in Aϩ␤Ϫ KPD patients.…”
Section: B Aϫ␤ϫmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, absence of GAD65 or IA-2 Abs, even in patients with long-standing diabetes, is probably quite reliable in classifying them as AϪ. To limit further the possibility of misclassifying Aϩ␤Ϫ KPD patients as AϪ␤Ϫ, we have performed extensive HLA typing (1,27) and have found that the frequencies of major class II alleles associated with susceptibility to autoimmune type 1 diabetes are not significantly higher in AϪ␤Ϫ KPD patients than in ethnicmatched population controls, whereas they are significantly higher in Aϩ␤Ϫ KPD patients.…”
Section: B Aϫ␤ϫmentioning
confidence: 99%
“…The longitudinal Houston cohort comprises over 500 multiethnic patients (44% African-American, 40% Hispanic, 15% Caucasian, 1% Asian), including 185 patients who have been followed for a mean of 5.5 yr (27). A comprehensive database compiles information on the natural history of all four groups of KPD.…”
Section: A Houstonmentioning
confidence: 99%
“…Several reports from sub-Saharan Africa [18-21] and the U.S. African-American population [22-25] have described atypical ketosis-prone "African" diabetes. While this clinical entity remains poorly defined, the common characteristics appear to include acute onset, often with ketoacidosis, in often obese adolescents or young adults with no islet autoantibodies and HLA genotypes inconsistent with T1aD.…”
Section: Ketosis-prone T1bdmentioning
confidence: 99%
“…Initial insulin therapy for type 2 diabetes patients is unusual unless the patient is markedly hyperglycemic and/or symptomatic [3,9,10,12]. Patients with ketosis prone diabetes (KPD) are in the category of those who present with ketocidosis but after initial insulin therapy can stop insulin and revert to tablet treatment [19]. The ORIGIN trial failed to find a role for low-dose insulin therapy early in the course of type 2 diabetes, in that insulin treatment did not reduce cardiovascular risk [20].…”
Section: Discussionmentioning
confidence: 99%